Llama (Lama glama) antiserum against SARS-CoV-2 - Stagnetto, Agustín (2022)
The receptor-binding domain (RBD) of SARS-CoV-2 Spike protein constitutes the key access for the virus inside the host cell. A positive correlation between titers of anti-RBD immunoglobulin G and antibodies (Ab) capable of neutralizing the virus has been demonstrated. In this context, passive immunotherapies such as convalescent plasma and hyperimmune equine serum have gained relevance as therapies against COVID-19. Another promising alternative is the use of polyclonal Ab from llamas (Lama glama), because of their unique features. For this reason, we aimed to obtain recombinant RBD as an immunogen to generate anti-RBD Ab in llamas. To achieve this, HEK 293 cells were transfected and transduced with the RDB encoding sequence, resulting in higher yields with this last method. The RBD was purified by affinity chromatography. An immunization schedule was designed and evaluated on two male animals, which were initially inoculated with RBD, followed by periodical boosters. Exploratory bleedings were performed in order to evaluate the reached titers, and larger bleedings in order to obtain enriched plasma with anti-RBD Ac. Ac quantification was accomplished by an “in-house” ELISA. Results showed that the immunization scheme was successful, achieving a maximum titer of 168000 at 28 days post-immunization. The results lay the foundations for the production of polyclonal anti-RBD Ab.